Obraz kryzysu migracyjnego na granicy polsko-białoruskiej na łamach polskich tygodników opinii „Newsweek”, „Wprost” i „Sieci” w latach 2021-2022 - Żmijkowska, Magdalena (Przegląd Wschodnioeuropejski, 2025)
The aim of this article was to analyze the portrayal of the migration crisis on the Polish Belarusian border in 2021-2022 in three Polish opinion weeklies: “Newsweek”, “Wprost”, and “Sieci”. The study aimed to determine the portrayal of events by each editorial office and whether the presented message reflected their ideological profile and political sentiments. Content analysis was used. The research results indicate that each editorial office constructed a different model of interpreting the crisis. “Newsweek” adopted a humanitarian-liberal framework, “Wprost” represented an ambivalent and analytical-political approach, and “Sieci” shaped a sovereign-nationalist narrative, emphasizing security issues, threats from Russia and Belarus, and heroizing the government and services as defenders of the border and national values. Consistent with their ideological orientation, the weeklies’ coverage not only differentiated the interpretation of the crisis but also reinforced social divisions in the perception of migrants, the role of the state, and responsibility for security.